Muscle Strength, Agility, and Body Composition in Children With Intestinal Failure on Parenteral Nutrition. Issue 4 (13th July 2022) - So, Stephanie; Patterson, Catherine; Betts, Zachary; Belza, Christina; Courtney-Martin, Glenda; Avitzur, Yaron; Wales, Paul W.
Abstract : Objectives: With increasing number of children with intestinal failure (IF) on long-term parenteral nutrition (PN), this study assesses the impact of IF on muscle strength, speed, and agility and body composition (BC), identifying clinical factors that may predict impairment. Methods: Cross-sectional study in children 5–18 years with IF on PN. Assessments included Bruininks-Oseretsky Test of Motor Proficiency-2 strength and agility subtest (BOT-2), and grip strength. BC data from dual-energy x-ray absorptiometry (DXA) measurements and clinical variables were collected by chart abstraction. Data were compared to age and sex matched controls and population norms. Results: Twenty-one children with IF (14 males), median age 8.33 (IQR: 6.96–11.04) years and 33 controls (20 males), 8.25 (6.67–10.79) years were included. Strength and agility ( P < 0.001) and grip strength ( P = 0.001) differed between groups. Nine of 21 (43%) of children with IF scored >1 standard deviation (SD) below mean on BOT-2 and 13 of 21 (62%) had grip strength >1 SD below mean. DXA measurements showed 10 of 18 (56%) of children had lower fat-free mass (FFM)% and higher fat mass (FM)% than reference norms. Decreased FFM% was associated with lower BOT-2 scores ( r = 0.479; P = 0.044) and grip strength scores >1 SD below mean ( P = 0.047). Additional clinical factors significantly impacting strength and agility included prematurity, height, hospitalizations, sepsis, and small bowel length. Conclusions: Children with IF are at risk of decreased muscle strength and agility, along with altered BC. Ongoing medical, nutritional, and rehabilitation intervention is vital to optimize outcomes.